INITIATIVES OF THE FAMOUS STATESMAN AND PUBLIC FIGURE TUROR RISKULOV IN THE SPHERE OF INTEGRATION OF THE ECONOMY OF TURKESTAN (TAMADDUN NURI JURNALI, 2024)
This article describes the initiatives and economic and social activities of Turar Riskulov, a well-known statesman and public figure, in the process of integrating the economies of Turkestan and Russia.The article also considers the development of transport in Turkestan, primarily rail, as a special period of integration of the economy of Turkestan, since it was found that it contributed to the establishment of broader integration ties with various regions of Turkestan.Russia.The economic and social activities of Turar Riskulov met the needs of increasing the production potential of the Turkestan economy and were of great importance for the republics of Central Asia.